An integration of reduction and logic for programming languages - Wright, David A (Rhodes University, Faculty of Science, Department of Computer Science, 1988)
A new declarative language is presented which captures the expressibility of both logic programming languages and functional languages. This is achieved by conditional graph rewriting, with full unification as the parameter passing mechanism. The syntax and semantics are described both formally and informally, and examples are offered to support the expressibility claim made above. The language design is of further interest due to its uniformity and the inclusion of a novel mechanism for type inference in the presence of derived type hierarchies
Keywords: Logic programming languages; Programming languages (Electronic computers)